Shuttle Breeding을 통한 벼 내냉성 유전자원 ‘중모1022’ - 김정주(Jeong-Ju Kim), 정응기(Eung-Gi Jeong), 정종민(Jong-Min Jeong), 이정희(Jeong-Heui Lee), 조영찬(Young-Chan Cho), 정오영(O-Young Jeong), 서대하(Dae-Ha Seo) (Korean journal of breeding, 2020)
‘Jungmo1022’, a japonica rice cultivar, was developed by a cross between ‘Jinbu31’ (IT212616) and ‘Gyodong23’ (IT213764) bythe rice breeding team at the National Institute of Crop Science, Korea, in 2000. ‘Jinbu31’ is tolerant to cold, and ‘Gyodong23’ is earlymaturing with high yield potential. The growth period of ‘Jungmo1022’ in paddy fields was 116 days on the North-middle highland in Korea,shorter than that of ‘Jinbu’. The culm length of ‘Jungmo1022’ was 67 cm, which was 2 cm shorter than that of ‘Jinbu’. There were 91spikelets per panicle in ‘Jungmo1022’. The elite line was developed by shuttle breeding in a cold screening field at Chuncheon and highlandJinbu sites in order to screen for cold tolerant varieties. Forty-five lines with more than 50% fertility were selected from the F2 generationin the cold screening field, and the line SR28990-B-2-2-2 was selected by the pedigree breeding method through F3-F7 generations cultivatedon the North-middle highland in Jinbu. During the yield trial conducted in 2008-2009 yield trial, an early heading, high-yielding, and coldtolerant line ‘Jinbu 48’ was selected for the local adaptability tests conducted from 2010 to 2012. The early maturing and cold-tolerant ‘Jinbu48’ was superior to ‘Jinbu’ in exhibiting shorter heading delay, reduced culm length, and spikelet fertility under cold temperature. The newline showed a milled rice productivity of 5.69 MT/ha at Jinbu sites under North-middle highland cultivation and was registered as a newcultivar ‘Jungmo1022’ (Registration No. 5563). KCI Citation Count: 2